Developing Application-Based Learning Media for Beginner Students - Syaprizal Syaprizal; Ardayati Ardayati (Edu-Ling: Journal of English Education and Linguistics, 2023)
Abstract The aim of this research was to develop an application-based learning media for Elementary School students to help them in learning English. Technology and information nowadays develop rapidly where the role of English is very crucial as a global language as well as the language of technology. This makes English one of elements to success in today's globalized world. English in Indonesia is still considered as a foreign language. In order to make English to be mastered as a communication tool, it is advisable to introduce English from an early age, especially at the Elementary School level. One way that can increase elementary school students' interest in getting to master English well is by developing various medium, especially application-based learning media that can be used on smartphones. Therefore, researchers developed Application-based Media to improve the English skills of IT Darussalam Muara Beliti Elementary School students. The results of this research were expected that the application-based learning media on smartphones to be used by teachers and elementary school students in the learning and teaching process. Keywords : developing, application-based learning, media